2002
DOI: 10.1557/jmr.2002.0459
|View full text |Cite
|
Sign up to set email alerts
|

Nickel–alumina nanocomposite powders prepared by novel in situchemical reduction

Abstract: Nanocomposite powders of Ni-Al 2 O 3 (5 and 10 vol% Ni) were prepared from porous alumina preforms with high specific area (100 m 2 и g −1 ) impregnated with nickel nitrate. Samples were obtained by reduction under a controlled oxygen partial pressure either directly or through an intermediate step, giving nickel aluminum spinel. In both cases, homogeneous dispersions of nickel particles in the alumina matrix were achieved. The Ni particle size ranged from 10 to 100 nm, depending on the preparation conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…After impregnation, the solvent is removed by evaporation and the nanoparticles precipitate inside. In this way, Al 2 O 3 -TiO 2 (titania nanoparticles in a porous alumina) [321,322], or alumina-nickel Al 2 O 3 -Ni (obtained by a reduction of NiO nanoparticles during annealing in hydrogen) [323] nanocomposites were prepared and studied.…”
Section: Development Of Novel Materials For Terahertz Opticsmentioning
confidence: 99%
“…After impregnation, the solvent is removed by evaporation and the nanoparticles precipitate inside. In this way, Al 2 O 3 -TiO 2 (titania nanoparticles in a porous alumina) [321,322], or alumina-nickel Al 2 O 3 -Ni (obtained by a reduction of NiO nanoparticles during annealing in hydrogen) [323] nanocomposites were prepared and studied.…”
Section: Development Of Novel Materials For Terahertz Opticsmentioning
confidence: 99%
“…Another route used was to reduce the spinel formed by the reaction discussed previously. Depending on the preparative route, the temperature of reduction (between 650 and 1025 °C) and the oxygen partial pressure (between 10 -8 to 10 -15 Pa), metallic particles have a size distribution varying from 10 to 100 nm [8]. These composites consist of Ni or Co particles dispersed in a porous matrix of submicronic -alumina or in a nanometric or phase, Fig.…”
Section: Al 2 O 3 -Oxide and Al 2 O 3 -Metal Nanocompositesmentioning
confidence: 99%
“…The formation and the stability of spinel and its capacity to be reduced seem to vary according to the reaction undertaken to form spinel, the stoichiometry and Al 2 O 3 -type. In [16], spinel was produced by solid state reaction with nanometric gamma phase alumina (γ-Al 2 O 3 ) impregnated with nickel nitrate (Νi(ΝΟ 3 ) 2 •6H 2 O), at temperatures ranging between 1,000°C and 1,300°C. The authors observed that the catalyst was totally reduced at temperatures higher than 950°C, with a mixture of CO and CO 2 as reducing atmosphere (and oxygen partial pressure of 1x10 -15 atm).…”
Section: Spinel Catalystmentioning
confidence: 99%